(untitled) (Raparin Journal of Humanities (RJH), 2024)
This paper, which is part of the requirements of an MA degree, is entitled "A Sociolinguistic Analysis of Ironic Expressions in English and Kurdish." It provides further insight into the sociolinguistic application of irony. Irony, which is categorized into verbal and situational is when something that was expected to have a specific result instead of results in a completely different or opposite outcome. The paper argues that expressing one thing while implying another is not always irony. In some instances, the ironic statement alludes to the fact that the idea being refuted is what underlies the truth of a situation, a claim, or a previous way of thinking. Data on Kurdish irony are gathered through observation and are explained in English, while data on English ironic expressions are collected from the corpus of English including books and online sources. The investigation of the topic is conducted using a descriptive methodology. Each sort of irony is described and illustrated, and the figurative connotation in both languages is also emphasized. The main objective of the study is to clarify the figurative meaning of irony in the two languages. The most significant findings comprise first, that irony has a positive connotation in literal contexts while it has a negative connotation in figurative contexts. Second, figurative language, which is frequently used in communication, contains irony. Additionally, ironic expressions are italicized in both languages.